Comparison of immune defense and antioxidant capacity between broodstock and hybrid offspring of juvenile shrimp (Macrobrachium nipponense): Response to acute ammonia stress. (18th March 2022) - Li, Yiming; Xiang, Yuqian; Jiang, Qichen; Yang, Ying; Huang, Yingying; Fan, Wujiang; Zhao, Yunlong
Abstract: Ammonia is a major environmental pollutant in the aquatic system that poses a great threat to the health of shrimp. Macrobrachium nipponense, as one of the large‐yield farmed shrimp, is facing germplasm degradation. Genetic improvement through hybridization is one of the effective methods to solve this problem. However, there are few studies on the effects of ammonia nitrogen on the germplasm resources of M .  nipponense . In this study, the broodstock populations (Dianshan, DS) and hybrid offspring (DS ♀ × CD [Changjiang, CJ ♂ × Dongting, DT ♀], SCD) were exposed to 0, 5, or 20 mg/L of ammonia for 96 h. The survival rate of the SCD group was greater than the DS group, although there were no significant differences in weight gain rate and length gain rate ( p  > 0.05). The number of positive cells and apoptosis rates in the DS group were significantly greater than in the SCD group after ammonia exposure ( p  < 0.05). As the ammonia concentration increased, the antioxidant enzyme activities in the SCD group were significantly higher than DS group, while the hepatotoxicity enzyme activities in the SCD group were significantly lower than DS group ( p  < 0.05). The trends in the expression of antioxidant‐ and immune‐related genes were generally consistent with the activities of antioxidant enzymes. Our study found that the hybrid population had stronger stress resistance than their parent populations at the same ammonia concentration. This study confirms our speculation that hybrid population has a greater advantage in antioxidant immunity, which also provides reference for the follow‐up study of chronic ammonia toxicity.